Rhesus macaque theta defensins suppress inflammatory cytokines and enhance survival in mouse models of bacteremic sepsis. - Justin B Schaal; Dat Tran; Patti Tran; George Ösapay; Katie Trinh; Kevin D Roberts; Kathleen M Brasky; Prasad Tongaonkar; André J Ouellette; Michael E Selsted (PLoS ONE, 2012)
Theta-defensins (θ-defensins) are macrocyclic antimicrobial peptides expressed in leukocytes of Old World monkeys. The peptides are broad spectrum microbicides in vitro and numerous θ-defensin isoforms have been identified in granulocytes of rhesus macaques and Olive baboons. Several mammalian α- and β-defensins, genetically related to θ-defensins, have proinflammatory and immune-activating properties that bridge innate and acquired immunity. In the current study we analyzed the immunoregulatory properties of rhesus θ-defensins 1-5 (RTDs 1-5). RTD-1, the most abundant θ-defensin in macaques, reduced the levels of TNF, IL-1α, IL-1β, IL-6, and IL-8 secreted by blood leukocytes stimulated by several TLR agonists. RTDs 1-5 suppressed levels of soluble TNF released by bacteria- or LPS-stimulated blood leukocytes and THP-1 monocytes. Despite their highly conserved conformation and amino acid sequences, the anti-TNF activities of RTDs 1-5 varied by as much as 10-fold. Systemically administered RTD-1 was non-toxic for BALB/c mice, and escalating intravenous doses were well tolerated and non-immunogenic in adult chimpanzees. The peptide was highly stable in serum and plasma. Single dose administration of RTD-1 at 5 mg/kg significantly improved survival of BALB/c mice with E. coli peritonitis and cecal ligation-and-puncture induced polymicrobial sepsis. Peptide treatment reduced serum levels of several inflammatory cytokines/chemokines in bacteremic animals. Collectively, these results indicate that the anti-inflammatory properties of θ-defensins in vitro and in vivo are mediated by the suppression of numerous proinflammatory cytokines and blockade of TNF release may be a primary effect.